Literasi Keuangan Dan Kontrol Diri Terhadap Perilaku Konsumtif Melalui Rasionalitas pada Mahasiswa Manajemen UIN Malang - Evy Nurlailatisy Syariifah; Indah Yuliana (Akuntansi & Ekonomika, 2022)
This “study aims to see the impact of financial literacy and self-control on consumptive behavior through rational. This study uses a quantitative approach with the object of research, namely Management Students of UIN Malang with Active Status in 2021. A sample of 132 people were obtained as samples after sampling using the Slovin formula. Then the data is processed using PLS software. The results of this study indicate that there is a negative and significant influence given by financial literacy and self-control on consumptive behavior. There is an influence given by rationality on consumptive behavior in a negative and significant way. Rationality mediates the effect of financial literacy and self-control on consumptive behavior.